Design and comparative in-vitro and in-vivo evaluation of starch-acrylate graft copolymer based salbutamol sulphate sustained release tablets - Kumar, Pankaj; Ganure, Ashok Laxmanrao; Subudhi, Bharat Bhushan; and et al (Shenyang Pharmaceutical University, 2014)
The present work deals with the development of controlled release tablets of salbutamol sulphate (SS) using graft copolymers of methyl methacrylate (St-g-PMMA and Ast-g-PMMA) on starch and acetylated starch. Formulations were evaluated for physical characteristics like hardness, friability, drug release, drug content and weight variations, which fulfilled all the official requirements of tablet dosage form. The release rates from formulated matrix tablets were studied at SGF (pH 1.2) followed by SIF (pH 6.8). Drug release from the graft copolymer based tablets was found to be sustained upto the 14 h with >75% drug release. The in-vitro release study showed that the graft copolymer based matrix formulations (F3 & F4) exhibited highest correlation value (r2) for higuchi kinetic model and Korsmeyer's model with n values between 0.61 and 0.67 proved that release mechanisms were governed by both diffusion and erosion mechanism. There was no significant difference in the pharmacokinetic parameters (tmax, Cmax, AUC, Ke, and t1/2) of the graft copolymers matrices and HPMC K100M matrix tablets, indicating their comparable sustained release effect. The potential of graft copolymers to sustain the drug release is well supported by in-vivo pharmacokinetic studies and their adequate physicochemical properties make them promising excipients for controlled drug delivery system.
Keywords: Acetylated starch; Graft copolymers; In vitro and in vivo; Korsmeyer's model; Methyl methacrylate; Salbutamol sulphate